FANATISME PENGGEMAR NADIN AMIZAH (ANALISIS ISI KONTEN PADA AKUN TIKTOK @CNADACC) - Irbah, Ais (Commsphere: Jurnal Mahasiswa Ilmu Komunikasi, 2024)
Nadin Amizah is a singer and songwriter who started his career in 2016 and is still active today. Nadin is an active singer who has just released an album entitled "For the World, Love and Dirt" on October 13 2023. Nadin Amizah has many fans spread across various regions in Indonesia and even abroad. On social media, especially TikTok, lots of Nadin fans post about Nadin, either at concerts or anything related to Nadin Amizah. Due to this, researchers are interested in studying research related to the fanaticism of Nadin Amizah's fans on TikTok social media. This research is qualitative research with content analysis, to interpret an idea or content to find out its relationship to the study being researched. The data collection techniques include documentation and observation. The subject of this research is the TikTok account of one of Nadin Amizah's fans, namely @cnadacc. The research results show that there is internal involvement and external involvement. Demonstrated internal involvement is manifested through loyalty, emotional attraction, sacrifice of time and energy. Meanwhile, their external involvement is realized through interactions built on social media and their activities, being involved in general activities related to their idols. Keywords: Fanaticism, Nadin Amizah, Fans, TikTok